Income inequality, economic growth, and the effect of redistribution - Klaus Gründler; Philipp Scheuermeyer (University of Würzburg, Department of Economics, 2015)
Evidence from a current panel of harmonized worldwide data highlights a robust negative effect of income inequality on economic growth that we trace back to its transmission channels. Less equal societies tend to have less educated populations and higher fertility rates, but not necessarily lower investment shares. The first two effects are harmful for growth and reinforced by limited credit availability. Higher public spending on education attenuates the negative effects of inequality. In addition to the inequality-growth relationship, we examine the direct influence of effective redistribution. When net inequality is held constant, public redistribution negatively affects economic growth. Redistribution hampers investment and raises fertility rates. Combining the negative direct growth effect and the indirect positive effect operating through lower net inequality, the overall impact of redistribution is insignificant. Whereas this result stems mainly from advanced economies, redistribution is beneficial for growth in low and middle-income countries.
Keywords: O11; O15; O47; H23; 330; Economic Growth; Redistribution; Inequality; Panel Data